2010
DOI: 10.2109/jcersj2.118.1021
|View full text |Cite
|
Sign up to set email alerts
|

Structure and photovoltaic activity of cupric oxide-based thin film solar cells

Abstract: Cupric oxide (CuO) thin films were prepared and their microstructures and photovoltaic properties were investigated. Thin film devices based on the CuO/C 60 heterojunction structure were fabricated on F-doped SnO 2 by spin-coating, and displayed photovoltaic activity under AM1.5 simulated sunlight conditions. The CuO thin film microstructure was examined using X-ray diffraction and transmission electron microscopy, which indicated the presence of CuO nanoparticles of size 1030 nm. The energy levels for the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 15 publications
1
9
0
1
Order By: Relevance
“…In order to fabricate high-performance Cu 2 O solar cells, it is vital to have excellent transport properties (carrier density and mobility, and minority carrier life time) inside Cu 2 O layer and at the junction interface. However, most Cu 2 O films have been prepared on un-textured or polycrystalline substrates by thermal oxidation, electro-deposition, and sputtering methods147891011121314151617181920. As a result, the films have a polycrystalline nature and rough surface morphologies, resulting in very defective films as well as poor interfaces at junctions and/or metal contacts comprising the cells.…”
mentioning
confidence: 99%
“…In order to fabricate high-performance Cu 2 O solar cells, it is vital to have excellent transport properties (carrier density and mobility, and minority carrier life time) inside Cu 2 O layer and at the junction interface. However, most Cu 2 O films have been prepared on un-textured or polycrystalline substrates by thermal oxidation, electro-deposition, and sputtering methods147891011121314151617181920. As a result, the films have a polycrystalline nature and rough surface morphologies, resulting in very defective films as well as poor interfaces at junctions and/or metal contacts comprising the cells.…”
mentioning
confidence: 99%
“…CuO has a preferred monoclinic structure, and its band gap ranges within 1.2eV-1.9eV [14]. CuO mostly possesses a direct band gap [2], [11], [13], although some studies have reported that CuO has an indirect band gap [14], [15]. The disparity in the findings of previous studies can be attributed to the complicated crystal structure of CuO and to the fact that CuO may belong to a particular class of compounds known as Mott insulators [16].…”
Section: Introductionmentioning
confidence: 93%
“…Motoyoshi fabricated junctions of FTO/CuO/C60 achieving an efficiency of 2.3 x10 --4 [26]. Mittiga achieved higher efficiencies (2 %) with a heterojunction of ITO/ZnO/Cu2O [13].…”
Section: Cuo X and Sno X Thin Filmsmentioning
confidence: 99%